Impact of economic shocks on mental health during COVID-19: A longitudinal study of adult residents of Indian metropolitan cities - Zakir Husain; Mousumi Dutta; Saswata Ghosh; Soumitra S. Datta (Indian Journal of Psychiatry)
Background: The causal impact of income shocks on mental well-being in developing countries is an under-researched area. The COVID-19 pandemic, along with the economic recession caused by the lockdowns to reduce transmission, provides a natural experimental setting to examine the causal impact of a decline in monthly per capita expenditure (MPCE) on mental health of the general population in India during the pandemic. Aim: To evaluate the impact of income shocks on mental health of adults in metro cities during the COVID-19 pandemic. Materials and Methods: The data were collected using the abridged version of the Depression Anxiety Stress Schedule administered through a telephonic survey on adult residents of six metropolitan cities in September–August 2020 and July–August 2021. Results: In the present study, 994 adults participated from six metropolitan cities. Average treatment effects were estimated using Propensity Score Matching. The mean normalized scores are significantly higher for respondents whose MPCE had fallen (treated) vis-à-vis respondents whose MPCE had remained same or increased (control): anxiety (0.21 for treated vs –0.19 for control), stress (0.16 vs –0.14), and depression (0.04 vs –0.19). Propensity score matching reveals that the normalized scores for anxiety, stress, and depression were 33 (95% confidence intervals, CI: 20.0–46.7), 25 (95% CI: 12.9–36.9), and 36 (95% CI: 18.6–53.1) higher among the treated group vis-a-vis control group. The ATET was 34 (95% CI: 18.9–48.9), 26 (95% CI: 10.1–42.9), and 32 (955 CI: 12.3–50.7) for these three outcomes, respectively. The post-estimation tests indicated that the results are valid. Conclusions: The study advocates that policies to ensure income security should be made an integral part of the response packages to tackle pandemics like COVID-19.